Exclusive interview with Prof. Dato' Dr. Koutoubou Moustapha Sano, Secretary General of International Islamic Fiqh Academy, OIC, Saudi Arabia, (PhD., AIKOL 1996) - U Tun Aung, Maulana Akbar Shah (2023)
An exclusive interview with Professor. Sanokoutoubou Moustapha Sano by Dr Maulana. it is coincides with 40th anniversaries of IIUM establishment. Dr Sano engaged in the process of IIUM from the beginning where he experienced as Master Students, PhD students, Lecturer, Professor, and finally he reached to the position of Deputy Rector of IIUM. in the later stage he went back to his own country and perform as the minister of Religious affairs and at present he is secretary general of International Islamic Judicial Law, Islamic Fiqh Academy, OIC, Suadiarabia.